Horizontal distribution of marine microbial communities in the North Pacific Subtropical Front - Lopes, Eva; Semedo, Miguel; Tomasino, Maria Paola; Mendes, Renato; de Sousa, João Borges; Magalhães, Catarina (Frontiers in Microbiology, 2024)
Microbial communities are crucial for important ecosystem functions in the open ocean, such as primary production and nutrient cycling. However, few studies have addressed the distribution of microplankton communities in the remote oligotrophic region of the Pacific Ocean. Moreover, the biogeochemical and physical drivers of microbial community structure are not fully understood in these areas. This research aims to investigate the patterns of prokaryotic and protists communities’ distribution in the North Pacific Subtropical Front (NPSF). The NPSF is a vast oligotrophic region with layered surface water and strong ocean currents. Despite its considerable size, its community distribution and function are poorly studied. We used a 16S and 18S rRNA gene sequencing approach to identify and characterize the water column microbial communities at two depths, the surface (3–5 m) and the deep chlorophyll maximum (DCM, 108–130 m). We aimed to elucidate the horizontal distribution patterns of these communities and to dissect the factors intricately shaping their distribution in the NPSF. Results showed that the community structure of both prokaryotes and protists was significantly influenced by depth, temperature, and longitude. Regarding alpha diversity, both communities presented a higher diversity at the surface. The prokaryotes also demonstrated to have a higher diversity in samples placed further east. The prokaryotes were dominated by Proteobacteria and Cyanobacteria, and the eukaryotic communities were dominated by Syndiniales. Combining biological and hydrographic data analysis showed the influence of vertical currents near the frontal jet in shaping the vertical distribution of both prokaryotic and protist communities. Even though most studies do not consider anomalies that emerge at each depth, these occurrences are capable of having a strong impact and influence on community structure. This study marks a significant advance in unraveling the intricate community structure and distribution dynamics of marine microbial communities within the North Pacific Ocean.